Characterization Red Palm Oil (RPO) Olein Fraction Via Distillation Vacuum - Jusman Jusman; Syamsuddin; Sri Handayani (RAFFLESIA JOURNAL OF NATURAL AND APPLIED SCIENCES, 2023)
Research has been carried out on the effect of red palm oil quality via vacuum pressure reduction distillation. In the initial stage, the crude palm oil (CPO) was centrifuged at 4000 rpm for 30 minutes to separate the olein and stearin fractions, then the olein fraction was treated to produce red palm oil via the stages of degumming process, neutralization, and a distillation process by reducing vacuum pressure. The use of the vacuum pressure reduction distillation method provides a significant effect in the red palm oil production process. Several parameters were analyzed, such as free fatty acid content, peroxide value, and carotene content, which had a significant effect on the quality of the red palm oil produced. From the results of the study showed that the free fatty acid content was in the range of 0.03 - 0.08%, the peroxide value was 0.11 - 0.15 meq/kg, and the carotene content was 467-586 ppm.